2019
DOI: 10.3389/fgene.2019.00153
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a progressive and devastating neurodegenerative disorder. It is the leading cause of dementia in the world’s rapidly growing aging population. The characteristics of AD are memory loss and cognitive impairment, meaning patients cannot carry out their daily activities independently. The increase of AD cases poses heavy burdens on families, society and the economy. Despite frequent efforts being made to research the etiology of AD, the causes of AD remain unknown, and no curative trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(83 citation statements)
references
References 91 publications
1
81
0
1
Order By: Relevance
“…The miRNAs could change the inflammatory responses via the regulation of gene expression by post-transcriptional modifications that cause degradation and inhibition of the translation of the molecular target [18,19,24]. Recent studies have shown that mature miRNAs could be potential biomarkers for diagnosis in many human diseases such as cancers, cardiovascular disease, and neurodegenerative disease [25][26][27][28]. In a study of IPF, the changes of miRNAs were demonstrated in the analysis of miRNA arrays containing probes for 450 miRNAs with isolated RNA from the lungs from patients with IPF or the control [29].…”
Section: The Role Of Mirna In Ipfmentioning
confidence: 99%
“…The miRNAs could change the inflammatory responses via the regulation of gene expression by post-transcriptional modifications that cause degradation and inhibition of the translation of the molecular target [18,19,24]. Recent studies have shown that mature miRNAs could be potential biomarkers for diagnosis in many human diseases such as cancers, cardiovascular disease, and neurodegenerative disease [25][26][27][28]. In a study of IPF, the changes of miRNAs were demonstrated in the analysis of miRNA arrays containing probes for 450 miRNAs with isolated RNA from the lungs from patients with IPF or the control [29].…”
Section: The Role Of Mirna In Ipfmentioning
confidence: 99%
“…MicroRNAs, particularly circulating microRNAs, have been found to be highly stable with long half-lives under a controlled environment [47,48]. Accumulating evidence from studies across broad biomedical disciplines suggests the involvement of microRNAs, and their potential applications as diagnostic as well as prognostic biomarkers in various human diseases including cancer [49][50][51], neurodegenerative diseases [52][53][54][55], fertility disorders [56,57], and metabolic disorders [58,59]. For several years, our research effort has been devoted to discovering potential applications of microRNAs in disease diagnosis, as well as elucidating the role of dysregulated microRNAs in cardiovascular pathogenesis [60][61][62][63][64].…”
Section: Micrornas the Small Nucleotides That May Play Big Roles In mentioning
confidence: 99%
“…Alzheimer's Disease (AD) is a neurodegenerative disorder characterized by the presence of two neuropathological features, namely the senile plaques, consisting of β-Amyloid peptides (Aβ), and the Neurofibrillary Tangles (NFTs), that contain highly phosphorylated microtubule-associated protein Tau [102]. The etiology and the molecular mechanisms driving AD pathogenesis are still poorly known (excess Aβ production or inefficient Aβ clearance and formation of NFT) [103]. Several studies support the hypothesis where the accumulation of Aβ leads to the generation of toxic aggregates, which results in neuronal dysfunction and, ultimately, cell death [102].…”
Section: Mirna: a Factor In Multifactorial Diseasesmentioning
confidence: 99%
“…Several miRNAs have been described to be involved at different stages of AD development, from the regulation of the Aβ or Tau protein production to their clearance. MiR-106a/520c, miR-20, miR-101, miR-16, and miR-153 can bind the 3 UTR of Amyloid Precursor Proteins (APPs), resulting in their lower expression, both in vitro and in vivo [103]. Alternatively, miR-29-a/b-1 and miR-29c were found to regulate Beta-Secretase Enzyme 1 (BACE1), the protease responsible for APP digestion [104].…”
Section: Mirna: a Factor In Multifactorial Diseasesmentioning
confidence: 99%